The Relationship Between Power and Culture and the Increase in Local Tax Revenue in South Lampung Regency - Rozi, Fachrur; Tomy, Chairian (Universitas Indonesia Mandiri, 2025)
Public awareness in fulfilling their tax obligations has not yet reached the level expected by the government. This study aims to determine the extent of the influence of power and culture on increasing local revenue (PAD) from the tax sector in South Lampung Regency. This research employs a qualitative method by analyzing documents, with data obtained from the Central Bureau of Statistics of South Lampung Regency. Data collection techniques include observing the development of the value of local revenue derived from the tax sector, as well as conducting interviews with individuals involved in each tax sector. The data is then analyzed, reduced, and presented using a SWOT analysis. The results show positive realization, as South Lampung Regency has implemented various tax service conveniences and developed systems to enhance revenue from the tax sector.